Factors That Influence Professional Quality of Life (Pro-QOL) on Clinical Nurses - Febrina Secsaria Handini; Fitriyanti Patarru'; Basilius Yosepfus Weu; Heryyanoor Heryyanoor; Sena Wahyu Purwanza (Jurnal Ners, 2019)
Introduction: Nurses are professionals that work by involving cognitive and emotional aspects simultaneously when providing nursing care, which provides both positive and negative experiences. These experiences can affect nurses' professional quality of life (Pro-QOL). Professional quality of life has three dimensions, namely burnout (BO), compassion satisfaction (CS) and Secondary Traumatic Stress (STS). This paper presents a systematic review of the literature that examined factors that influence the professional quality of life on clinical nurses.Methods: Articles are obtained from the Scopus, Science Direct and Emerald databases using keywords Compassion Satisfaction, Burnout, Secondary Traumatic Stress, Nurse. The search identified 69 articles and 15 relevant research articles published between 2014-2019.Results: The results show that the inability of nurses to control the core of self-evaluation and the five-factor model (FFM) of personality traits, high workload, pressure in the work and imbalance between rewards and work, coping nurses and poor emotional support, rejection and giving up behavior can increase the number of those with compassion fatigue.Conclusion: The results show that the inability of nurses to control the core of self-evaluation and the five-factor model (FFM) of personality traits, high workload, pressure in the work and imbalance between rewards and work, coping nurses and poor emotional support, rejection and giving up behavior can increase the number of those with compassion fatigue.